2009
DOI: 10.1002/fedr.200911118
|View full text |Cite
|
Sign up to set email alerts
|

Pollen types of the Egyptian species of the genus Salvia (Lamiaceae)

Abstract: Pollen morphology of seven species of genus Salvia (Lamiaceae) was investigated using light and scanning electron microscopy. Pollen was studied to show all possible characteristic features like shape, size, apertures, wall stratification, etc., with special reference to the specific characters of each pollen type. Four pollen types were recognized viz. Salvia aegyptiaca pollen type, Salvia deserti pollen type, Salvia palaestina pollen type and Salvia spinosa pollen type. Description of each type, a key to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…An operculum with granule was seen in all the taxa (Figures 1-3). Similarly, some authors (Perveen and Qaiser, 2003;Moon et al, 2008c;Hassan et al, 2009) found colpi with granulate membranes and pointed, acute, and obtuse ends. The exine is semitectate (Walker, 1974;Hamzaoğlu et al, 2005;Jafari and Nikian, 2008) and muri are simply columellate (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…An operculum with granule was seen in all the taxa (Figures 1-3). Similarly, some authors (Perveen and Qaiser, 2003;Moon et al, 2008c;Hassan et al, 2009) found colpi with granulate membranes and pointed, acute, and obtuse ends. The exine is semitectate (Walker, 1974;Hamzaoğlu et al, 2005;Jafari and Nikian, 2008) and muri are simply columellate (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 76%
“…Hymenosphace (Table 2; Figure 1). Hamzaoğlu et al (2005), using the Wodehouse method, and Moon et al (2008c) and Hassan et al (2009), using the acetolyzed method, found some differences in the size and shape of the Salvia species examined. These differences can be mainly caused by different preparation techniques.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations